Study of Light Pollution in Urban Lighting in Nisantasi Example - EVREN KORKMAZER; YASIN BEKTAS; MERVEBANU AYKANAT; SHARGIYAYA JEVEDZADE; GOKÇEN FIRDEVS YÜCEL CAYMAZ (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
To make urban identity-forming components visible by making use of technologic improvements, and to make the city livable for everybody by enhancing aesthetic and charming attraction are becoming important for urban designers. Lighting is becoming an important factor to suit cities to livable places for livings in all comfort conditions. By the improvement of science and technology, to organize the life spaces of livings according to today’s comfort conditions are considered more and more important. Urban lighting is affecting both the lighting comfort and livings’ (humans, animal, and plants) health in many dimensions. The light used on the unsuitable spot, unsuitable direction, unsuitable amount and unsuitable time is defined as light pollution. Within the scope of this study, national and international literature research related to urban lighting is done and basing criteria are identified. In the frame of these identified criteria, Nisantasi example is examined in the context of lighting pollution. Important streets and lanes and important historical and religious structures that gained a seat in public memory are identified. Designing criteria of the lighting tools existing in these identified areas and their suitability according to their spot are evaluated and measuring their illuminance sufficiency, the issues which are detected as light pollution are stated. In conclusion, the studies done in our country are cited and the issues that are to be done to prevent light pollution are introduced as a suggestion.